The evolution of Colombian industry in the context of the energy-mining boom: Symptoms of the dutch disease? (2016)
This paper seeks to evaluate and demonstrate the hypothesis of deindustrialization and Dutch Disease (DD) for the case of the Colombian economy by using a Beta regression model. The results of the research indicate that it is not possible to reject the suggestion that the mining and energy boom have potential adverse effects on the manufacturing sector.